AICCRA-RUFORUM-WASCAL partnership advances climate-smart higher education in Africa benefitting over 2,300 University lecturers in 37 African countries - Segnon, Alcade; Zougmore, Robert (2024)
Through AICCRA partnership and engagement, WASCAL and RUFORUM developed new climate-smart agriculture (CSA) and climate information services (CIS) university course modules, informed by CGIAR science, benefitting over 2,300 university lecturers—29% women—in 37 African countries. These modules were integrated into three BSc programs (Sokoine University of Agriculture, Tanzania) and a newly created MSc specialization (Felix Houphouet Boigny University, Cote d’Ivoire); and informed a new MSc program (Makerere University, Uganda) on Green Economy and Climate Finance, ultimately generating future expertise to transform African agriculture and food systems.